Μελέτη αντιοξειδωτικής δράσης και συνολικών φαινολικών συστατικών σε ερυθρούς οίνους Κυπριακών γηγενών και ξένων ποικιλιών - Τσιολάκκη, Αμαλία (Τμήμα Γεωπονικών Επιστημών, Βιοτεχνολογίας και Επιστήμης Τροφίμων, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
This study investigated the antioxidant capacity and the quantification of total phenolic components in Cypriot wines of red indigenous and foreign varieties. Phenolic ingredients contribute to aroma, color and taste. Specifically, varieties of maratheftiko, Mavro, ofthalmo, and Cabernet Sauvingnon were examined. Antioxidant capacity was determined by the DPPH• method and the total phenolic components by the Folin - Ciocalteu method. The results obtained from this study were as following: The highest antioxidant capacity is recorded for the variety maratheftiko and the smallest one for the variety ofthalmo. In addition, the highest concentration of total phenolic components is found in maratheftiko and Cabernet Sauvingnon, while the lowest concentration is in Mavro and ofthalmo. The highest concentration of total phenolic components is not always the same as the highest antioxidant capacity. Attention is also given to the type of phenolic ingredients present in wines.
Keywords: Wine; Phenolic compounds; Antioxidant capacity; Varieties; DPPH; Folin - Ciocalteu; Κρασί; Φαινολικά συστατικά; Αντιοξειδωτική ικανότητα; Ποικιλίες